Studi Analisis Konsep Ideologi Marhaenisme Sukarno Sebagai Asas Perjuangan Bangsa Indonesia - Pratama, Febri Fajar; Asyiah, Ai Kusmiati; Chandra, Deni (Department of Pancasila and Civic Education, Universitas Negeri Medan, 2022)
AbstractIdeology is important in the order of social and state life. Philosophically, the concept of ideology is very subjective. There are those who consider ideology as dogma, while others are concerned with linking ideology as political discourse and political views. Meanwhile, some think that ideology is based on the concrete interests of social class which is marked by the absence of interest on an economic basis. In the socio-historical context of the Indonesian nation, ideology is used as a